Novel Alterations of Some Mitochondrial tRNA Genes in Vietnamese Colorectal Cancer Patients - Bich, Pham Thi; Van, Nguyen Thi; To, Ta Van; Thai, Trinh Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2, 2019)
Abstract: Some mutations of mt-DNA which encode tRNA (mt-tRNA) were previously reported to be associated with clinical manifestations of neuromuscular disorders syndrome. In addition, alterations of the mitochondrial genome have been suggested to contribute to mitochondrial dysfunction and tumorigenesis. Alterations in some mt-tRNA genes have also been identified in breast cancer, lung cancer and colorectal cancer. However, so far, there has not been any report on mt-tRNA gene alteration in the Vietnamese colorectal cancer patients. This study analyzes the alterations of some mt-tRNA genes in a group of Vietnamese colorectal cancer patients and predicts the influence of the alterations on the secondary structure of tRNA based on bioinformatic tools. PCR-RFLP and DNA sequencing methods were used to screen alterations; the secondary structure of tRNA was predicted in silico by using a tool of the Vienna RNA Websuite. The study results show that both A12309G and A12310G of tRNA Leu were identified together in two out of 98 patients, and both T12150G and C12154G of tRNA His were identified in one out of 19 patients. [1] All these alterations are heteroplasmic and have not been reported in cancer patients so far. In particular, the C12154G alteration in the DHR loop led to changes in the secondary structure of tRNA His and could affect the function of this tRNA molecule. Keywords : mt-tRNA, Vietnamese colorectal cancer, PCR-RFLP, DNA sequencing. References : [1] International Agency for Research on Cancer. https://gco.iarc.fr/today/fact-sheets-cancers Colorectal cancer (accessed 30 November 2018). [2] M. Brandon, P. Baldi, D.C Wallace, Mitochodrial mutations in cancer, Oncogene 25(34) (2006) 4647 - 4662. http://doi.org/ 10.1038/sj.onc.1209607. G. Li, Y.X. Duan, X.B. Zhang, F. Wu, Mitochondrial RNA mutations may be infrequent in hepatocellular carcinoma patients, Genet. Mol. Res. 15(2) (2016) 1-7. http://doi.org/ 10.4238/ gmr.15027665. [4] F. Mohammed, A.R. Rezaee, E. Mosaieby, M. Houshmand, Mitochondrial A12308G alteration in RNA Leu (CUN) in colorectal cancer samples, Diagn. Pathol. (2015) 10-115. http://doi.org/10. 1186/s13000-015-0337-6. [5] S. Datta, M. Majumder, N.K. Biswas, N. Sikdar, B. Roy, Increased risk of oral cancer in relation to common Indian mitochondrial polymorphisms and Autosomal GSTP1 locus, Cancer. 110 (2007) 1991-1999. http://doi.org/ 10.1002/cncr.23016. [6] L. Wang , Z.J. Chen , Y.K. Zhang , H.B. Le, The role of mitochondrial RNA mutations in lung cancer, Int. J. Clin. Exp. Med. 8 (8) (2015) 1-7. http://doi.org/ 10.3389/fgene.2014.00158. [7] A.R. Gruber, R. Lorenz, S.H. Bernhart, R. Neubock, I.L Hofacker, The Vienna ARN Websuite, Nucleic Acids Res. 36 (2008) 70-74. http: /doi.org/10.1093/ nar/gkn188. [8] Basic Local Alignment Search Tool. https://blast. ncbi.nlm.nih.gov/Blast.cgi/ nucleotide Blast (accessed 11 November 2018). [9] Y. Goto, I. Nonaka, S. Horai, A mutation in the RNALeu (UUR) gene associated with the MELAS subgroup of mitochondrial encephalomyopathies, Nature 348 (6302) (1990) 651-653. http://doi.org/ 10.1038/348651a0. [10] A human mitochondrial genome database. http://www.mitomap.org/MITOMAP (accessed 11 November 2018). [11] A. Lorenc, J.B. Golik P, Homoplasmic MELAS A3243G mtDNA mutation in a colon cancer sample, Mitochondrion 3 (2) (2003) 119-124. https://doi.org/ 10.1016/S1567-7249(03)00106-5. [12] E.L. Blakely, J.W. Yarham, C.L. Alston, K. Craig, J. Poulton, C. Brierley, S.M. Park, A. Compston, C. Allen, S. Sharif , P. Enevoldso, M. Wilson, D.M. Turnbull, R.M. cFarland, R.W.Taylor, Pathogenic mitochondrial tRNA point mutations: nine novel mutations affirm their importance as a cause of mitochondrial disease, Hum. Mutat. 34 (9) (2013) 1260- 2068. https://doi.org/10.1002. [13] S. DiMauro, Mitochondrial ADN medicine, Biosci. Rep. 27 (3) (2007) 5-9. https://doi.org 10.1007/ s10540 -007-9032-5. [14] D.C. Wallace, D. Chalkia, Mitochondrial ADN genetics and the heteroplasmy conundrum in evolution and disease, Cold Spring Harb Perspect Biol. 5 (11) (2013) 1-7. https://doi.org 10.1101/cshperspect. a021220.